Completion of the Special Dictionary for Law Enforcement Science – Schedule, Approach (Academic Journal of Internal Affairs, 2020)
About the great undertaking of completion a historical work for a profession the first short survey was given in a publication of dr. Szabolcs Mátyás, the secretary of the editorial committee in the study collection issued on the 15th anniversary of the Hungarian Association for Law Enforcement Science, under the title: „A Few Thoughts about the Completion of the Special Dictionary for Law Enforcement Science” (Mátyás, 2019). This summary explains the approach accommodated to the schedule of completion of the special dictionary. The process of creation will be presented by objective facts, frankly, sometimes with own emotions added, from points of view of the editors. Beside the obligatory reporting of the project it gives information about the works of altogether 167 participants, elaborators, peer reviewers, translators, editors and other contributors, for the birth of a special scientific product.
Keywords: special dictionary; law enforcement science